Inception and espousal of knowledge management in IT companies of Bangalore. - Chethana Ramesh. (2008)
This research set out to answer the question: What is the extent of adoption of Knowledge Management in IT companies of Bangalore? It sought to answer this question in terms of KM tools and technology used; KM processes and procedures.